The Role of Private Military Companies in Defense Policy and Military Operations - Sarjito, Aris (Andalas Journal of International Studies (AJIS), 2023)
This research explores the role of private military companies (PMCs) in defense policy and military operations. This research utilizes a qualitative approach, primarily relying on secondary data sources such as government reports, academic articles, and legal documents. The findings highlight PMCs' diverse legal and regulatory landscape, including international conventions and national legislation. These frameworks aim to provide oversight and accountability for the activities of PMCs, addressing their status, recruitment, and operational limitations. Furthermore, the study highlights the ethical considerations associated with using PMCs, such as human rights abuses, transparency, and accountability issues. Lastly, it uncovers the geopolitical implications of relying on PMCs, including the potential erosion of state sovereignty, regional power dynamics, and the risk of conflict escalation.